Exploring the learning climate in anaesthesiology training hospitals in Ireland. Issue 11 (2nd November 2020) - Walshe, Criona M; Flaherty, Gerard
Abstract : Background: Learning climate is defined as the learners' perception of their environment. There is growing evidence that learning climate is a major determinant of trainee behaviour. This mixed methods study evaluated the learning climate in anaesthesiology training hospitals in Ireland. Methods: Through sequential explanatory strategy, learning climate was measured using a validated 40-item questionnaire, which was completed by 118 anaesthesiology trainees from eight training hospitals in Ireland. This was followed by two focus group interviews with 16 participants. Qualitative interpretations were derived using framework analysis. Results: The mean learning climate score was from the questionnaire 116 (+/−15.7) out of 160. The highest level of satisfaction recorded was for the perception of atmosphere (scoring 76% of the maximum score), while learning opportunities ranked lowest (67% of the maximum score). Three key themes emerged from the focus groups: lack of resources, the transient nature of the job and the sense of a gap between consultants and trainees. Conclusions: Overall there was an acceptable learning climate in training hospitals in Ireland, but satisfaction levels may vary and lack of learning opportunities appears to be a significant issue for trainees.